Religious Narratives in Italian Literature after the Second Vatican Council A Semiotic Analysis - Ponzo, Jenny (De Gruyter, 2019)
This book presents a semiotic study of the re-elaboration of Christian narratives and values in a corpus of Italian novels published after the Second Vatican Council (1960s). It tackles the complex set of ideas expressed by Italian writers about the biblical narration of human origins and traditional religious language and ritual, the perceived clash between the immanent and transcendent nature and role of the Church,